Plasma tumor necrosis factor-α is associated with sarcopenia in elderly individuals residing in agricultural and pastoral areas of Xinjiang, China - Wumaer, Aishanjiang; Maimaitiwusiman, Zhuoya; Xiao, Wenwen; Xuekelati, Saiyare; Liu, Jinling; Musha, Tajiguli; Wang, Hongmei (Frontiers in Medicine, 2022)
Background Inflammatory reactions play a significant role in the occurrence and development of sarcopenia. Determining the association between specific cytokines and sarcopenia may reveal the disease’s pathophysiological mechanism(s). Accordingly, the present study aimed to investigate the association between sarcopenia and inflammatory cytokines among the elderly natural population in agricultural and pastoral areas of Xinjiang. Methods We conducted a cross-sectional epidemiological survey of the community-dwelling older people using a multi-stage random sampling method in Mulei County in northern Xinjiang and Luopu County in southern Xinjiang from September 2017 to May 2018. Of the 2,100 participants, the statistical analyses included 1,838 participants with complete data. Comparisons of living habits, disease status, biochemical indexes, and levels of interleukin (IL)-4, IL-6, IL-8, IL-10, and tumor necrosis factor (TNF)-α in sarcopenia and non-sarcopenia participants were made in this study. Results Our study revealed no significant differences (i.e., P > 0.05) in sex, age, ethnicity, smoking and drinking habits, serum renal function, total cholesterol, and diabetes in the elderly between the sarcopenia and non-sarcopenia groups in Xinjiang. However, triglyceride levels (P = 0.004), hypertension (P = 0.019), and abdominal obesity (P < 0.001) in the sarcopenia group were significantly higher than those in the non-sarcopenia group. Moreover, the levels of IL-10 (P < 0.001), IL-4 (P < 0.001), and TNF-α (P < 0.001) in the sarcopenia group were higher than those in the non-sarcopenia group after adjusting for sex, age, hypertension, blood lipid concentration, and obesity. Furthermore, after adjusting for sex, age, hypertension, obesity, and IL-10, IL-4, and IL-6 levels, an increased TNF-α level was also significantly associated with sarcopenia. Conclusion The results of the present study suggest that an increased plasma level of TNF-α is significantly associated with sarcopenia among elderly individuals residing in Xinjiang’s agricultural and pastoral areas. Further study is still needed to determine the physiological role of “immune aging” in the pathogenesis of sarcopenia.